2011
DOI: 10.1021/es202570g
|View full text |Cite
|
Sign up to set email alerts
|

Sequestration of Zinc from Zinc Oxide Nanoparticles and Life Cycle Effects in the Sediment Dweller Amphipod Corophium volutator

Abstract: We studied the effects of ZnO nanoparticles [ZnO NPs, primary particle size 35 ± 10 nm (circular diameter, TEM)], bulk [160 ± 81 nm (circular diameter, TEM)], and Zn ions (from ZnCl(2)) on mortality, growth, and reproductive endpoints in the sediment dwelling marine amphipod Corophium volutator over a complete lifecycle (100 days). ZnO NPs were characterized by size, aggregation, morphology, dissolution, and surface properties. ZnO NPs underwent aggregation and partial dissolution in the seawater exposure medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
48
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(48 citation statements)
references
References 35 publications
0
48
0
Order By: Relevance
“…In the latter case, however, the study was conducted without bottom sediments. Fabrega et al (2012) also observed its negative influence on the growth and reproduction of the amphipod Corophium volutator. The activity of dissolved ions from NPs is reported as one of the main reasons responsible for the toxic effects of NPs (Adams et al 2006;Beer et al 2012;Yang et al 2012).…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…In the latter case, however, the study was conducted without bottom sediments. Fabrega et al (2012) also observed its negative influence on the growth and reproduction of the amphipod Corophium volutator. The activity of dissolved ions from NPs is reported as one of the main reasons responsible for the toxic effects of NPs (Adams et al 2006;Beer et al 2012;Yang et al 2012).…”
Section: Discussionmentioning
confidence: 92%
“…Only a few studies have shown the toxicity of various NPs present in bottom sediments in relation to sedimentdwelling organisms (Oberholster et al 2011;Coleman et al 2013;Hanna et al 2013). These studies have dealt with nanoZnO (Buffet et al 2012;Fabrega et al 2012;Hanna et al 2013), with a lack of data on the toxicity of nano-Ni. Our research revealed significant mortality of H. incongruens in the sediments containing both nano-ZnO and nano-Ni.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to their relatively high sensitivity to contaminants and their ecological importance, amphipods are frequently used to test sediment toxicity (Schlekat et al, 1992;Lenihan and Oliver, 1995;DeWitt et al, 2001). Nevertheless, few tests of nanomaterial toxicity with amphipods are published, and of these only two were conducted in sediments (Fabrega et al, 2011;Mwangi et al, 2011).…”
Section: Introductionmentioning
confidence: 99%